An Analysis of Perlocutionary Speech Acts: Case Study in the 2024 Presidential Candidate Debate - Miranda, Tiara; Dharmawan, Yanuarius (Indonesian Journal Publisher, 2025)
This study explores the use of perlocutionary speech acts by presidential candidates during the 2024 presidential debate, focusing on the types employed, their frequency, and how cultural backgrounds influence interpretation. Using a qualitative descriptive method, the research analyzed the third segment of the first 2024 debate, aired on December 12, 2023. The findings identified 24 instances of perlocutionary speech acts, including actions such as embarrassing, irritating, persuading, attracting attention, deceiving, and encouraging. These acts demonstrate the strategic use of language to achieve specific effects on the audience. Moreover, the study highlights that cultural values, ethnic backgrounds, and political experiences significantly shape candidates' interpretations and responses to these speech acts. The research provides insights into the interplay between language use and cultural influences in political communication, offering a deeper understanding of rhetorical strategies in high-stakes political discourse